Epidemiology of bloodstream infections in a Scottish haemodialysis population with focus on vascular access method. (April 2021) - Crowe, K.; White, B.; Khanna, N.; Cooke, B.; Kingsmore, D.B.; Jackson, A.; Stevenson, K.S.; Kasthuri, R.; Thomson, P.C.
Summary: Background: Infection is the second highest cause of mortality in end-stage renal disease, with a significant proportion relating to haemodialysis (HD) vascular access-related infection (VARI). Aim: To report the rate and antimicrobial resistance (AMR) of all-source bloodstream infections (BSIs) by vascular access type in a Scottish HD cohort. Methods: Retrospective analysis was undertaken of data on adult patients attending seven HD units during 2017. Total HD days for each vascular access type were calculated. BSIs were analysed with rates expressed per 1000 HD days. AMR was verified using health board microbiology databases. Findings: Excluding contaminant organisms, there was an overall BSI rate of 0.57 per 1000 HD days. The highest all-source and vascular access-related infection (VARI) BSI rates per 1000 HD days were in the non-tunnelled central venous catheter (CVC) group (3.11 and 2.07 respectively), followed by tunnelled CVC (1.10 and 0.67), arteriovenous graft (0.51 and 0.31), and finally arteriovenous fistula (0.29 and 0.02). The non-VARI BSI rates were lowest in the arteriovenous graft group. Staphylococci comprised the majority of events, with Staphylococcus aureus implicated in 29%. Gram-negative BSIs were prevalent, particularly in CVC groups, and associated with higher mortality. Multidrug-resistant (MDR) S. aureus and carbapenem resistance were relatively low. MDR Gram-negatives were high compared with the Scottish population. Conclusion: Arteriovenous fistula access is confirmed as having lowest all-source and VARI BSI rates, and arteriovenous graft access the lowest non-VARI BSI rates. Staphylococci remain the prevailing genus; however, the contributions of Gram-negative BSIs, the higher mortality, and proportion of MDR organisms in this group are notable.